A consumption theory and task–fitness perspective of wireless internet adoption for mobile commerce. (10th April 2015) - Ahluwalia, Punit; Gimpel, Gregory; Varshney, Upkar
Recent advances in wireless technology have resulted in new opportunities for electronic commerce to migrate to mobile platforms. To understand the acceptance of mobile commerce, we investigate the drivers of the adoption of wireless internet broadband for the laptop. Task fitness is important to those users conducting mobile commerce, which may involve completion of several sequential transactions. This study draws upon consumption theory and task–technology fit literature to investigate the antecedents of wireless internet adoption. The structural equation model of field study data indicates that there are significant positive relationships among perceived quality, task fitness, and perceived value and the intention to adopt wireless internet. Surprisingly, the study also finds that the likelihood to subscribe to wireless internet declines as the awareness about the technology increases. This research provides theoretical insights for researchers and practical guidance for service providers as they push mobile commerce to increase data traffic revenue.